Left atrial strain: A useful index in atrial fibrillation. (1st October 2016) - Cameli, Matteo; Mandoli, Giulia Elena; Loiacono, Ferdinando; Sparla, Stefania; Iardino, Elisabetta; Mondillo, Sergio
Abstract: Left atrial (LA) strain is a speckle tracking echocardiography (STE)-derived parameter applied to the analysis of chamber function that provides highly reproducible measures of LA deformation by a non-Doppler, angle-independent quantification. In recent years, data regarding accuracy and clinical application of LA strain are rapidly increasing. This review describes the main features of LA strain and examines the role of STE in the evaluation of various aspects of AF, as the risk of developing the arrhythmia in general population, the evaluation of LA fibrosis and LA impairment, the quantification of cardioembolic risk and of recurrence after cardioversion or ablation therapies. Highlights: Speckle tracking echocardiography has shown high feasibility and reproducibility. Left atrial strain is useful in atrial fibrillation diagnosis and followup. Integrating strain in echo evaluation of these patients increases accuracy.